Francisca Álvarez González, A Pioneer of Adults’ Literacy in La Coruña - Alfaya Lamas, Elena (Rastros Rostros, 2021)
The path to equality is full of women whose work and contribution to social wellbeing has remained invisible. It is our aim to restore the still living memory of an entrepreneur and pioneering woman providing adults’ literacy skills and basic education: Mrs. Francisca Álvarez González. Previous research on her is minimum and that is one of the main reasons why we have decided to restore of her memory from oblivion. Our methodological research strategy has been qualitative. We have reconstructed her life history by means of several unstructured interviews and an examination of personal documentation belonging to the family archive. She was an Orensian pioneer for alphabetization in La Coruña and Cambre. She contributed not only to its inhabitants’ education but also to the economic growth of the area. Our findings show the huge impact of this Galician woman on her area of influence, more complex than thought. This research gives back to History a part of the biography of one of our great women
Keywords: woman; gender; adults' education; Francisca Álvarez González; literacy skills